The role of medicinal plants in the treatment of Coronavirus infections (Annals of the Institute of Biology, 2022)
The coronavirus family consists of numerous species that cause respiratory and gastrointestinal infections in vertebrates, but some members such as SARS, MERS, and SARS-CoV-2 are particularly dangerous to humans. So far, SARS-CoV-2 is confirmed in 636.440.663 patients worldwide, and it is responsible for 6.606.624 deaths. Plants possess a number of chemical constituents, which act as inhibitors of viral proteins and can be used in the treatment of viral diseases, with a lower rate of virus resistance. The retrospective investigation covered a period of 27 years, from 1995 to 2022 and it is implemented through the analysis of results from previously reported studies focused on alternative anti-coronavirus agents. The total of 73 plant species from 46 families, with reported anti-coronavirus activity, was noted. Considering the number of species with anti-coronavirus effects, the most prevalent family was Fabaceae with 9.59%. Many bioactive compounds were secondary metabolites, and the vast majority was isolated from leaves. The anti-coronavirus activity of plant products was recorded against six coronaviruses: SARS-CoV, SARS-CoV-2, MERS-CoV, BCV, HCoV-OC43, and HCoV-NL63. Among the mechanisms of antiviral action, the inhibition of 3-chymotrypsin-like protease, 3Clpro was frequently described. This study illustrated the high potential of plants and their products in terms of anti-coronaviral compounds. Since viruses represent molecular pathogens, with high mutations range as well as resistance to synthetic antiviral drugs, a novel investigation should be oriented towards the isolation and characterization of efficient antiviral agents of natural origin.